Reflections on the Past, Present, and Future of IUU Fishing under International Law - Oral, Nilufer (Martinus Nijhoff Publ, 2020)
The present brief contribution reflects on the evolution of mu fishing, its current status, and possible future pathways to prevent, deter, and eliminate this practice. IUU fishing not only presents a question of management and conservation, but also entails serious human rights and transnational crime components. From these perspectives, this paper concludes that IUU fishing must be addressed through a multi-regime and multi-institutional process requiring the involvement of many stakeholders, including non-State actors. In particular, the effective settlement of IUU fishing disputes requires enhancing the role of international courts and tribunals as part of this process.
Keywords: Iuu Fishing; Human Rights; Transnational Crime; Non-State Actors; İnternational Courts And Tribunals